The many faces of CD8+ T cells in atherosclerosis. Issue 5 (October 2018) - van Duijn, Janine; Kuiper, Johan; Slütter, Bram
Abstract : Purpose of review: Atherosclerosis and the clinical consequence of cardiovascular disease remain the leading cause of death worldwide. Both an increase in cholesterol levels, as well as immune responses drive the pathogenesis of this disease. Although much is known about the role of many immune cell subsets in atherogenesis, research into the role of CD8 + T cells is limited. Recent findings: Both atheroprotective and atherogenic functions of CD8 + T cells have been reported. On the one hand, the inflammatory cytokines produced by CD8 + T cells exacerbate inflammatory responses, and the cytotoxic activity of these cells toward lesion-stabilizing cells such as endothelial cells drives the progression and instability of atherosclerotic lesions. On the other hand, cytotoxic activity toward antigen presenting cells and the presence of regulatory CD8 + T-cell subsets dampen immunity and can limit atherosclerosis. Summary: Here we review the different roles of CD8 + T cells in atherosclerosis and discuss possible treatment strategies targeting these cells to reduce atherosclerotic lesion burden.